Implementasi Program Pengabdian Masyarakat dalam Mempertahankan Perayaan Tradisi 10 Muharam di Desa Kancing Kecamatan Karang Tinggi Kabupaten Bengkulu Tegah - Ikke Wulan Dari; Nabila Isnaini; Aldsy Pujita Sari; hani, muhammad hanif; Della Oktavia; Fadila Dwi Rahmatika; Nova Julita; Natiara Oktavia; Khairul Hidayah (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This community service activity in the form of a lively celebration of 10 Muharram 1446 H was carried out thanks to the cooperation of Fatmawati Sukarno Bengkulu students and the Kancing village community, Karang Tinggi sub-district, Central Bengkulu Regency in an effort to celebrate 10 Muharram while maintaining Islamic values ​​and raising the spirit of children in Kancing village in learning to recite the Qur'an. The method used was to hold competitions for the children of Kancing village, such as the MTQ competition, the adzan competition, etc. which were held at the Mujahidin mosque in Kancing Village. This service aims to provide a forum for preserving festival customs, as well as providing inspiration and increasing religious understanding and self-confidence in order to encourage participants to actively memorize and study the Qur'an. The residents of Kancing Village still practice the custom of celebrating the 10th of Muharram. The Kancing Village Regional Government plays an important role in maintaining the 10th Muharram custom among today's Muslim community.